НАЦІОНАЛЬНИЙ ЧИННИК У РОЗБУДОВІ АВТОНОМІЇ В КРИМУ (1991 – 1997 рр.) (Zaporizhzhia Historical Review, 2021)
The article is dedicated to the elucidating the national movements of the Crimea tatars and their activity dealing with the creating of national-cultural societies in the period of 1991-1997